ANALISIS KINERJA PEGAWAI DI PERUM PERHUTANI DIVISI REGIONAL JAWA TENGAH (Studi Kasus : Biro SDM Perum Perhutani Divisi Regional Jawa Tengah) - Amelia, Sheila Rachmita; Hariani, Dyah (Journal of Public Policy and Management Review, 2016)
Employee performance is the work of someone who assessed in terms of quality, quantity, cooperation, and good punctuality in carrying out its duties optimally. The factors that drive and constrain the performance of employees, among others abilities, mental attitude, communication and leadership. This study aimed to describe and analyze the performance of employees in Perum Perhutani Central Java Regional Division as well as to determine the factors that drive and impede the performance of employees in Perum Perhutani Central Java Regional Division. This research uses descriptive qualitative research method. The data in this study were obtained from observation, interviews and documentation. The results of this study indicate that the performance of employees in Perum Perhutani Regional Division of Central Java is already quite good but there are still shortcomings in terms of quality, quantity and timeliness On the capability of employees average - average already graduate and get a wide range of education and training to support the ability of employees. On the mental attitude factor is still there are employees who received disciplinary punishment. In the communication factors, communication is established already well underway. On the factor of leadership, the leadership has provided direction and support to the employees, conduct regular evaluations, as well as help employees who are having difficulty. The advice given is centralized and the server should not be added in order not to hamper the timely completion of tasks and applications in the employee assessment should be upgraded in order not to run slowly. Employees must have a good attitude so that no employee received disciplinary punishment back.